Challenges in the implementation of the local content curriculum in urban schools - Kasman Kasman; Firdaus Firdaus (Himpunan Pengembang Kurikulum Indonesia, 2025)
The Local Content Curriculum (LCC) plays a crucial role in strengthening cultural identity and enhancing the relevance of education in multicultural societies. However, its implementation in urban schools, particularly in Makassar City, faces significant challenges. This study aims to identify the main obstacles in LCC implementation, considering socio-cultural dynamics, resource availability, educational policies, and student perceptions. Using a qualitative approach with a case study design, data was gathered through semi-structured interviews with teachers, principals, and students, non-participant observations, and document analysis. Thematic analysis was applied to interpret the data. The findings reveal four key obstacles: misalignment between instructional content and students' diverse cultural backgrounds, limited resources and teacher training, a centralized curriculum policy, and students' perceptions of LCC as irrelevant to their academic futures. Based on these findings, the study recommends reformulating national education policies to provide more autonomy for schools in designing relevant local curricula. It also urges the government to offer ongoing, locally responsive teacher training and ensure the availability of contextual learning materials. At the implementation level, schools and teachers should adopt pedagogical strategies that link local content with students' social realities, fostering meaningful and empowering learning experiences. Abstrak Kurikulum Muatan Lokal (KML) memiliki peran strategis dalam memperkuat identitas budaya dan meningkatkan relevansi pendidikan di masyarakat multikultural, namun pelaksanaannya di sekolah-sekolah perkotaan, seperti di Kota Makassar, masih menghadapi berbagai kendala yang kompleks. Penelitian ini bertujuan untuk mengidentifikasi hambatan utama dalam implementasi KML dari aspek sosial-budaya, sumber daya, kebijakan pendidikan, dan persepsi peserta didik. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui wawancara semi-terstruktur dengan guru, kepala sekolah, dan peserta didik, observasi non-partisipan, serta studi dokumen. Analisis data dilakukan secara tematik. Hasil penelitian menunjukkan empat kendala utama: ketidaksesuaian materi dengan latar belakang budaya peserta didik yang heterogen, keterbatasan sumber daya dan pelatihan guru, kebijakan kurikulum yang terlalu terpusat, serta persepsi peserta didik terhadap relevansi KML yang rendah. Berdasarkan temuan tersebut, rekomendasi kebijakan yang disarankan mencakup perlunya reformulasi kebijakan pendidikan nasional yang memberi ruang struktural dan otonomi lebih luas kepada sekolah dalam menyusun kurikulum lokal yang relevan. Pemerintah juga perlu menyediakan pelatihan guru yang berkelanjutan dan berbasis kebutuhan lokal, serta menjamin ketersediaan bahan ajar kontekstual. Di tingkat pelaksana, sekolah dan guru disarankan untuk menerapkan strategi pedagogis yang mengaitkan muatan lokal dengan realitas sosial peserta didik guna menciptakan pembelajaran yang bermakna dan berdaya guna. Kata Kunci: implementasi kurikulum; muatan lokal; sekolah perkotaan